Pharmacochemical Insights of Pedalium Murex L. With Emphasis on Recent Formulations, Phytochemistry and Biological Activities - Surinderjeet Kaur,; Isha,; Mandeep Kaur,; Seema Sharma,; Dr. Naresh Singh Gill, (Asian Journal of Pharmaceutical Research and Development, 2026)
Pedalium murex Linn. (Family: Zygophyllaceae), commonly known as Bada Gokhru in Hindi and Large Caltrops in English, is a remarkable annual herb widely distributed across arid and semi-arid regions of India, Sri Lanka, Pakistan, and parts of Africa. It has been esteemed in traditional systems of medicine Ayurveda, Unani, and Siddha chiefly for its diuretic, aphrodisiac, anti-urolithiatic, and tonic properties. The plant, particularly its spiny fruits, is rich in diverse phytochemicals including saponins, flavonoids (quercetin, luteolin), alkaloids, sterols (β-sitosterol), tannins, terpenoids (ursolic acid), mucilage, and fixed oils. Scientific validation of its traditional claims has intensified over the past two decades, revealing potent antioxidant, antimicrobial, anti-inflammatory, hepatoprotective, analgesic, antidiabetic, hypolipidaemic, anticancer, and wound-healing activities. Recent pharmaceutical research has focused on development of novel drug delivery systems nanoparticles, phytosomes, liposomal gels, transdermal patches, and PLGA microspheres to overcome limitations of bioavailability and stability. This review comprehensively discusses the botanical, phytochemical, pharmacological, and formulation aspects of Pedalium murex, with particular emphasis on advancements in the last decade.